(untitled) (Revista de Estudos da Linguagem, 2024)
several studies state that the comprehension of the meaning of language is based on concrete and modal simulations. This assertion is evidenced by the activation of sensorimotor brain areas during the processing of movement-related linguistic stimuli. This paper aims to review the literature on embodied simulation as a mechanism for comprehending concrete and abstract language. A literature search was conducted in major international databases for articles related to embodied simulation from the fields of neuroscience and psycholinguistics. In this regard, the article presents a section on embodied simulation as a condition for language comprehension, as well as empirical evidence from neuroscience regarding the activations of sensory and motor areas during the simulation for such comprehension. Subsequently, studies are presented in the psycholinguistic framework that account for these simulation processes in the comprehension of abstract language, more specifically, metaphorical language, taking into account the Conceptual Metaphor Theory. Finally, the evidence presented in the literature reviewed leads one to conclude that simulation is one of the key elements for comprehending concrete and abstract language, as in the case of metaphor. However, for such comprehension, other elements are required such as association, mental images, and imagination that allow for the recreation of abstract concepts that do not directly relate to embodied experiences.